The causal role between phasic midbrain dopamine signals and learning - Aquili, Luca * (2014)
The article discusses how phasic dopamine (DA) may relate to action selection, goal-directed behavior, and behavioral flexibility of a mice. It states that optogenetic targeting of midbrain DA cells and striatal projections showed role in reward prediction and behavioral flexibility. It notes that DA activity regulates aspects related to appetitive reward learning. It mentions that DA is causally involved in flexible behavioral adaptations that occur due to changes in stimulus-reward incident.